2018
DOI: 10.1590/s1517-707620180004.0564
|View full text |Cite
|
Sign up to set email alerts
|

Influência da alumina sintetizada por reação de combustão nas propriedades de compósitos com matriz de polipropileno

Abstract: RESUMO O polipropileno (PP) é um dos polímeros mais utilizados em produtos manufaturados em plásticos, por isso, estudos em compósitos têm sido realizados na tentativa de modificar suas propriedades e ampliar ainda mais seu uso. Portanto, este trabalho teve como objetivo utilizar alumina sintetizada por reação de combustão em laboratório e avaliar sua influência em concentrações de 1, 3 e 5 pcr (partes por cem de resina), nas propriedades de compósitos com matriz de PP. A alumina sintetizada foi misturada ao P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…The XRDs of α‐Al 2 O 3 standard (ICSD 25778) and all samples produced in this study are shown in Figure S1. The samples present the characteristic peaks, according to the pattern obtained from the ICSD database, of the corundum‐like crystal structure of α‐Al 2 O 3 at: 25.6° (0 1 2); 35.2° (1 0 4); 37.8° (1 1 0); 43.4° (1 1 3); 52.6° (0 2 4); 57.5° (1 1 6); 66.5° (2 1 4); 68.3° (3 0 0); and 76.9° (1 0 10) corresponding to the alpha alumina crystallographic phase without the presence of secondary phases 22,23 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The XRDs of α‐Al 2 O 3 standard (ICSD 25778) and all samples produced in this study are shown in Figure S1. The samples present the characteristic peaks, according to the pattern obtained from the ICSD database, of the corundum‐like crystal structure of α‐Al 2 O 3 at: 25.6° (0 1 2); 35.2° (1 0 4); 37.8° (1 1 0); 43.4° (1 1 3); 52.6° (0 2 4); 57.5° (1 1 6); 66.5° (2 1 4); 68.3° (3 0 0); and 76.9° (1 0 10) corresponding to the alpha alumina crystallographic phase without the presence of secondary phases 22,23 …”
Section: Resultsmentioning
confidence: 99%
“…According to Alves et al. , the precursor has a significant influence on the formation of the crystalline domain of the structure after sintering the monoliths 23 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polypropylene (PP) is one of the most important thermoplastics in the polymer industry, with a wide range of applications; it is a relatively lower cost resin, with low density, good processability, corrosion resistance, high crystallinity, and excellent permeability to water and CO 2 , properties that are translated into one of the most worldwide-consumed polymers [1][2][3][4]. Nevertheless, the large production, together with inappropriate discharge, have contributed to seriously damage the environment, mainly in big cities, where flooding and urban pollution are clearly seen [5][6][7].…”
Section: Introductionmentioning
confidence: 99%